Use of statistical methods in detecting accounting engineering activities (as exemplified by the accounting system in Poland) - Second part: Empirical aspects of analysis - Leszek Michalczyk (e-Finanse: Financial Internet Quarterly, 2013)
This article is one in a series of two publications concerning detection of accounting engineering operations in use. Its conclusions and methods may be applied to external auditing procedures. The aim of the present duo-article is to define a method of statistical analysis that could identify procedures falling within the scope of a framework herein defined as accounting engineering. This model for analysis is meant to be employed in these aspects of initial financial and accounting audit in a business enterprise that have to do with isolating the influence of variant accounting solutions, which are a consequence of the settlement method chosen by the enterprise. Materials for statistical analysis were divided into groups according to the field in which a given company operated. In this article, we accept and elaborate on the premise that significant differences in financial results may be solely a result of either expansive policy on new markets or the acquisition of cheaper sources for operating activities. In the remaining cases, the choice of valuation and settlement methods becomes crucial; the greater the deviations, the more essential this choice becomes. Even though the research materials we analyze are regionally-conditioned, the model may find its application in other accounting systems, provided that it has been appropriately implemented. Furthermore, the article defines an innovative concept of variant accounting.
Keywords: D21; L20; M21; M41; 330; Polish accounting system; accounting engineering; variant accounting; theory of accounting aspects